When Nonsense Makes Sense: Scribal Habits in the Space-intervals, Sense-pauses, and Other Visual Features in P46 - Ebojo, Edgar Battad (The Bible translator, 2013)
This article explores the visual and paratextual features embedded in P46, and assesses how these reflect a microcosm of ancient book production enterprise as well as its eventual construal by the reading community that used it. Accordingly, it also suggests ways in which the copying habits of the scribe who produced this manuscript may be similarly unveiled through these features.